Análisis de mercado para la exportación de papachina - malanga, producida en el ecuador para el consumo en el mercado estadounidense - Lescano Lara, Yessenia Katherine (2014)
Malanga in Ecuador is a non-traditional product, is a tuber that gives us lots of nutritional content such as calcium, protein, iron, fiber and more. Ecuador is a country where agriculture generates employment and foreign exchange, thanks to the contributions of agricultural production. In provinces such as Sto. Domingo, El Oro, Pastaza among others, are producers of taro, and they found a source of income is still a demand for export of potatoes. It is well to look for strategies to increase production in the country , Because it has a climate , soils and geography suitable for cultivation, you have the opportunity to export all year to different countries where other suppliers of malanga not have year-round supply problems in climate, it becomes difficult for the cultivation and harvesting…